NUMERICAL MODELING, VALIDATION AND OPTIMIZATION OF FIXING DEVICES FOR STEERING MECHANISMS - C. S. Ferreira, Ana Paula; F. C. Machado, Ewald Carlos (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
The laboratories of the automotive industry need to test the internal systems of vehicles to check strength and durability. An example is the steering mechanism, which is fastened at a device with high resistance, and subjected to loads of great intensity. These fixing devices are generally conceived without a proper structural analysis and optimization. This work presents a practical project where the goal is to verify if two existing devices are undersized or oversized. They are modeled by finite element method and the numerical model is validated with experimental data. Optimization is done in order to propose more efficient configurations for these devices.